High-pressure-assisted X-ray-induced damage as a new route for chemical and structural synthesis. Issue 28 (5th June 2018) - Evlyukhin, Egor; Kim, Eunja; Goldberger, David; Cifligu, Petrika; Schyck, Sarah; Weck, Philippe F.; Pravica, Michael
Abstract : A novel structural and chemical synthesis of Cs–O derived materials has been demonstrated via X-ray irradiation of Cs2 C2 H2 O5 at high pressure. Abstract : X-ray induced damage has been known for decades and has largely been viewed as a tremendous nuisance. We, on the other hand, harness the highly ionizing and penetrating properties of hard X-rays to initiate novel decomposition and synthetic chemistry. Here, we show that powdered cesium oxalate monohydrate pressurized to ≤0.5 GPa and irradiated with X-rays of energies near the cesium K-edge undergoes molecular and structural transformations with one of the final products exhibiting a new type of bcc crystal structure that has previously not been observed. Additionally, based on cascades of ultrafast electronic relaxation steps triggered by the absorption of one X-ray photon, we propose a model explaining the X-ray induced damage of multitype bounded matter. As X-rays are ubiquitous, these results show promise in the preparation of novel compounds and novel structures that are inaccessible via conventional methods. They may offer insight into the formation of complex organic compounds in outer space.